Adult outcomes by parental, school and postcode aggregated income in childhood-A descriptive analysis of the cohorts 1981-1989 in Finland. - Aapo Hiilamo; Niilo Luotonen; Lauri Mäkinen; Tiina Ristikari (PLoS ONE, 2025)
Monitoring the ways in which childhood socioeconomic environment is associated with adult outcomes is fundamental in terms of informing evidence-based debates. However, we know little about the cohort differences in the association of childhood income with adult outcomes in Finland, a country of low economic inequality and one of the most desegregated educational systems in the OECD countries. We use register data on cohorts born in 1981-89. We divide these cohorts into tenths by their parental, school and postcode-level aggregated income at the age of 15. We focus on five adult outcomes at the age of 30. On average across the cohorts, compared to the highest income groups, the lowest tenth of parental, school and postcode income had, respectively, a 1.8, 1.7 and 1.4-fold risk of death, 3, 1.3 and 0.9-fold risk of low education, 2.5, 1.8, and 1.4-fold risk of long-term unemployment. People with a lower childhood parental or school income were more likely to live with a partner and have children than people from higher income backgrounds. The differences by school and postcode income in the education outcome were small. We observe increasing differences in the education and employment outcomes by parental and, to a lesser extent, school income.